Poster for the Tea n' Baskets storytelling sessions, 2012. - Jarvis, Dale Gilbert (2012)
Poster for the Tea n' Baskets storytelling sessions held in Corner Brook, Newfoundland, March 18, 2012 and in Grand Falls-Windsor, Newfoundland, March 25, 2012.